Incremental prognostic value of pericoronary adipose tissue attenuation on top of comprehensive CCTA assessment. (25th November 2020) - Van Diemen, P.A; Bom, M.J; Driessen, R.S; Everaars, H; Schumacher, S.P; De Winter, R.W; Van De Ven, P.M; Freiman, M; Goshen, L; Heitel, D; Langzam, E; Van Rossum, A.C; et al.
Abstract: Background: Coronary computed tomography angiography (CCTA) derived parameters linked to severity and extent of atherosclerosis are associated with prognosis in patients with coronary artery disease (CAD). Furthermore, coronary inflammation, by determining pericoronary adipose tissue CT-attenuation (PCATa), can be assessed on CCTA as well and has been proposed as promising prognostic marker. Objective: To assess the prognostic value of PCATa on top of traditional CCTA derived atherosclerotic parameters. Methods: A total of 543 patients who underwent CCTA because of suspected CAD and in whom follow-up was obtained were included. CCTA assessment comprised; coronary artery calcium score (CACS), presence of obstructive CAD (≥50% stenosis) and high-risk plaques (HRP), total plaque volume (TPV), non-calcified plaque volume (NCPV), and PCATa. The endpoint was a composite of death and non-fatal myocardial infarction (MI). Optimal prognostic thresholds were determined for quantitative CCTA variables. Univariable Cox regression analyses were performed to determine clinical characteristics and CCTA variables associated with the endpoint, a subsequent multivariable Cox regression analysis that included variables associated with the endpoint was used to determine independent predictors of the endpoint. An additional Cox regression analysis was performed to test the incremental prognostic value of CCTA variables over clinical characteristics, significance of each sequentially added variable was tested using the likelihood ratio test. Results: During a median follow-up time of 6.6 [interquartile range: 4.7–7.8] years, a total of 42 (20 MI/22 death) (8%) patients suffered an endpoint. CACS >83.2, obstructive CAD, HRP, TPV >269mm 3, and NCPV >83mm 3 were all associated with occurrence of the endpoint with unadujsted hazard ratio's (HR) of; 5.37, 5.70, 3.31, 7.76, and 6.77, respectively (p<0.001 for all). PCATa of the RCA above −74.4 Hounsfield units (HU) had a detrimental effect on prognosis (unadjusted HR: 1.99, p=0.037), while PCATa of the LAD nor Cx was associated with outcome (Log-rank p-value 0.255 and 0.218, respectively). PCATa of the RCA remained an independent predictor of death and MI when incorporated in a multivariable analysis inlcuding all CCTA variables and clincal chacteristics associated with the endpoint (adjusted HR: 2.11, p=0.024). Furthermore, adding PCATa of the RCA to a model that included clinical characteristics and all CCTA parameters led to an improvement of the prognostic value of the model (change in Chi-square = 4.45, p=0.035) (figure). Conclusion: Coronary inflammation of the RCA determined by PCATa provides incremental prognostic value on top of traditional CCTA parameters linked to extent and severity of CAD. Funding Acknowledgement: Type of funding source: None